A distinctive subset of PEComas harbors TFE3 gene fusions - Argani, Pedram; Aulmann, Sebastian; Illei, Peter B.; Netto, George J.; Ro, Jae; Cho, Hyun-yee; Dogan, Snjezana; Ladanyi, Marc; Martignoni, Guido; Goldblum, John R.; Weiss, Sharon W. (The American journal of surgical pathology, 2010)
Perivascular epithelioid cell neoplasms (PEComas) include the common renal angiomyolipoma, pulmonary clear cell sugar tumor, lymphangioleiomyomatosis, and less common neoplasms of soft tissue, gynecologic, and gastrointestinal tracts. Recently, aberrant immunoreactivity for TFE3 protein (a sensitive and specific marker of neoplasms harboring TFE3 gene fusions) has been reported in as many as 100% of PEComas; however, TFE3 gene status in these neoplasms has not been systematically investigated. We used a fluorescence in situ hybridization (FISH) break-apart assay to evaluate for evidence of TFE3 gene fusions in archival material from 29 PEComas. These cases included 2 earlier published TFE3 immunoreactive nonrenal PEComas, 14 additional nonrenal PEComas, and 13 renal angiomyolipomas with predominantly spindle or epithelioid morphology. Four nonrenal PEComas (mean patient age 24 y) showed TFE3 gene rearrangements by FISH, and all 4 of these showed strong positive (3+) TFE3 immunoreactivity using the original validated overnight incubation protocol. Two of these cases had adequate mRNA for RT-PCR analysis, but neither harbored the PSF-TFE3 gene fusion reported earlier in 1 PEComa. In addition, a lung metastasis of a uterine PEComa showed TFE3 gene amplification, an earlier unreported phenomenon. None of the other 24 PEComas (mean patient age 54 y) showed TFE3 gene alterations, though 4 exhibited moderate positive (2+) TFE3 immunoreactivity. In contrast, using an automated stainer, 2 of these 4 cases exhibited strong (3+) TFE3 immunoreactivity. All PEComas with TFE3 genetic alterations immunolabeled strongly for Cathepsin K, similar to other PEComas. In conclusion, a subset of lesions currently classified as PEComas harbors TFE3 gene fusions. Although numbers are small, distinctive features of these cases include a tendency to young age, the absence of association with tuberous sclerosis, predominant alveolar architecture and epithelioid cytology, minimal immunoreactivity for muscle markers, and strong (3+) TFE3 immunoreactivity. Despite significant morphologic and immunohistochemical overlap with other PEComas, PEComas harboring TFE3 gene fusions may represent a distinctive entity.
Gesehen am 25.11.2022